The Influence of Environment and Satisfaction on Student Learning Motivation - Ibrahim, Ely; Napu, Karlina; Darman, Darman (Westscience Press, 2023)
This study aims to identify the influence of environment and satisfaction on student learning motivation at Bina Mandiri University, Gorontalo. Motivated students have a higher success rate in completing their studies. Therefore, understanding the factors that influence student learning motivation is important in efforts to improve the quality of education. This research method uses a quantitative approach by collecting data through questionnaires distributed to Bina Mandiri University Gorontalo students. The research sample consisted of 93 respondents who were randomly selected from various study programs. Data analysis was performed using multiple linear regression techniques. The results of the study show that the university environment has a negative and insignificant influence on student learning motivation. While student satisfaction has a positive and significant influence on student learning motivation.